2003
DOI: 10.1140/epje/i2003-10045-3
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualisation of homogeneous and heterogeneous crystallisation in an ensemble of confined domains of poly(ethylene oxide)

Abstract: We present a study of homogeneous and heterogeneous nucleation in polymer crystallisation. In bulk samples the crystallization is typically dominated by nucleation from defects (heterogeneous nucleation), and consequently studies must rely on sample preparation to minimize this effect. We present a study of nucleation within discrete droplets of poly(ethylene oxide) that are formed by the dewetting of a thin film on an unfavourable substrate. The samples provide an ensemble of impurity-free droplets, with leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
83
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 40 publications
10
83
1
Order By: Relevance
“…The melting behavior can be fitted into a sigmoidal plot where half of the crystals melt at ΔT 50% ¼ 0.1°C. Our observation of a cumulative distribution of melting resembles experiments on crystal nucleation in which samples comprised of small separate droplets were observed (24)(25)(26). In the case of melting nucleation, the crystals can be in the same droplet due to the fact that melting of one crystal does not induce melting of a nearby crystal.…”
Section: Resultssupporting
confidence: 71%
“…The melting behavior can be fitted into a sigmoidal plot where half of the crystals melt at ΔT 50% ¼ 0.1°C. Our observation of a cumulative distribution of melting resembles experiments on crystal nucleation in which samples comprised of small separate droplets were observed (24)(25)(26). In the case of melting nucleation, the crystals can be in the same droplet due to the fact that melting of one crystal does not induce melting of a nearby crystal.…”
Section: Resultssupporting
confidence: 71%
“…8,10 The transition occurs over a 5 8C range, which is expected because each domain must create its own nucleus, and this is a process that has been shown to occur stochastically. 8,28 In agreement with the findings of Röttele et al, 15 we also have observed a wide temperature range (%5 8C) over which melting occurs. This has been attributed to the fact that individual domains exist in various metastable states, having been formed under such large supercoolings.…”
Section: Resultssupporting
confidence: 92%
“…We focus on confined systems since they can provide a deep understanding of crystallization processes inside this material, because the confinement volume approaches intrinsic lengths of the phenomenon studied. 5,11 In this article, the crystallization activity energy of PCL under spatial confinement was shown much lower than that of PCL in bulk, and this provides a model to explain the phenomenon of double-melting peak for PCL. The nonisothermal crystallization kinetics of PCL in bulk and PMMA/ PCL (85/15) blend was investigated by two kinetic approaches which have been proposed to predict and analyze nonisothermal crystallization kinetics.…”
Section: Introductionmentioning
confidence: 85%